PROFIL ANTROPOMETRIK DAN FITNESS PEMAIN BOLAVOLI PUTERI SDN MOJOWUKU I KEDAMEAN GRESIK - Nining Widyah Kusnanik, (Arena, 2010)
The aim of this research is to evaluate the anthropometrical and physical performance of the female volleyball players at SDN Mojowuku I Kedamean Gresik. This study was conducted on 15 female volleyball players who has won national competition. Data was collected by test and measurement on anthropometric including height, body mass, sitting height, reaching height, and length of leg ; physical performance including explosive power ( vertical jump), speed (sprint 18m) and agility (shuttle run 8m). Data was analysis by using mean and standard deviation.             The result of this study was found that mean of height, body mass, sitting height, reaching height, and length of leg the players were 157,6±0,6 cm, 27,0±1,0 kg, 84,7±0,7 cm, 198,2±0,7 cm, 91,8±1,1 cm, and 155,2±0,7 cm., respectively. Mean vertical jump, leg strength, and back strength of the players were74,5±6,5cm, 173,6±34,1kg, and 136,2±20,4kg, respectively. Mean explosive power ( vertical jump), speed (sprint 18m) and agility (shuttle run 8m) were 27,5±2,6 cm, 5,2±0,2 seconds,  and 14,8±0,3 seconds, respectively. It can be concluded that the female volleyball players have a high posture but they were less in explosive power ability.